Peran BUM Desa dalam Penguatan Tata Kelola Desa wisata di Desa Toyomarto Singosari Kabupaten Malang - Maryunani; Shofwan; Jamal, Badrul (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This study examines the role of Village-Owned Enterprises (BUM Desa) in strengthening the governance of tourist villages in Toyomarto Village, Singosari District, Malang Regency. Tourist villages are one of the strategies for developing community-based tourism that has the potential to improve the village economy. BUM Desa, as a village economic institution, is expected to be a driving force in the management and development of village tourism potential. This study uses a qualitative method with a case study approach to analyze the role of BUM Desa in the aspects of planning, organizing, implementing, and supervising the governance of tourist villages. The results of the study indicate that BUM Desa has a significant contribution in strengthening community capacity, developing tourism infrastructure, and increasing village original income through the management of tourist villages. However, there are several challenges that need to be overcome, such as limited human resources and coordination between stakeholders. This study provides recommendations for optimizing the role of BUM Desa in strengthening the governance of tourist villages in Toyomarto Village.